Fibulin‐5 regulates keloid‐derived fibroblast‐like cells through integrin beta‐1. (14th July 2015) - Furie, N.; Shteynberg, D.; Elkhatib, R.; Perry, L.; Ullmann, Y.; Feferman, Y.; Preis, M.; Flugelman, M. Y.; Tzchori, I.
Synopsis: Objective: Keloid scar is pathological tissue that appears after skin injury, and that is more aggressive than hypertrophic scars. Keloid scars are characterized by increased proliferation of fibroblast‐like cells (FLCs) and the accumulation of extracellular matrix, mainly collagen. Fibulin‐5, a glycoprotein secreted by many cell types, is a component of the extracellular matrix. We investigated the effect of fibulin‐5 on the adhesion and proliferation of FLCs derived from keloid scars and the role of integrin beta‐1 in these activities. Methods: Fibroblast‐like cells were isolated from six keloid scars and cultured on plates coated with fibulin‐5 or with gelatin. Cells were incubated for 72–96 h to examine proliferation rates and incubated for 240 min, with washings at 20, 40, 60, 90, 120, 180 min, to assess adhesion rates. To examine the role of integrin beta‐1, the anti‐human integrin beta‐1 (CD29) antibody was added to the culture medium. Results: Fibroblast‐like cells from keloids cultured on a fibulin‐5‐coated surface showed a significantly reduced proliferation rate and a delayed adhesion rate, compared to cells cultured on gelatin‐coated dishes. Adherence of these cells to fibulin‐5 pre‐coated wells was significantly reduced in the presence of anti‐human integrin beta‐1 (CD29) antibodies. Our current findings are similar to previously observed reduced proliferation in vascular smooth muscle cells overexpressing fibulin‐5. We did not test the effects of fibulin‐5 on normal fibroblasts. Conclusion: This study demonstrates the pivotal role of the extracellular protein, fibulin‐5, on the adhesion and proliferation of human keloid‐derived cells, through binding to integrin beta‐1.